Exercise Does Not Protect against Peripheral and Central Effects of a High Cholesterol Diet Given Ad libitum in Old ApoE−/− Mice - Di Cataldo, Vanessa; Géloën, Alain; Langlois, Jean-Baptiste; Chauveau, Fabien; Thézé, Benoît; Hubert, Violaine; Wiart, Marlène; Chirico, Erica N.; Rieusset, Jennifer; Vidal, Hubert; Pialoux, Vincent; Canet-Soulas, Emmanuelle (Frontiers in Physiology, 2016)
Aim: Advanced atherosclerosis increases inflammation and stroke risk in the cerebral vasculature. Exercise is known to improve cardio-metabolic profiles when associated with a caloric restriction, but it remains debated whether it is still beneficial without the dietary control. The aim of this study was to determine both the peripheral and central effects of exercise training combined with a cholesterol-rich diet given ad libitum in old ApoE-/- mice. Methods: 45-weeks old obese ApoE-/-mice fed with a high cholesterol diet ad libitum were divided into Exercise-trained (EX; running wheel free access) and Sedentary (SED) groups. Insulin tolerance and brain imaging were performed before and after the twelve-weeks training. Tissue insulin resistance, oxidative stress and inflammation markers in plasma, aorta and brain were then assessed. Results: In EX ApoE-/- mice, no beneficial effect of exercise was observed on weight, abdominal fat, metabolic parameters, oxidative stress, or inflammation compared to SED. Despite the regular exercise training in ApoE-/- EX mice (mean of 12.5 km/week during twelve weeks), brain inflammation imaging score was significantly associated with increased blood brain barrier (BBB) leakage evaluated by imaging follow-up (r²=0.87; p=0.049) with a faster evolution compared to SED ApoE-/-mice. Conclusion: We conclude that in a context of high cardio-metabolic risk, exercise does not provide any protective effect in old ApoE-/- animals under high cholesterol diet given ad libitum. Peripheral (insulin sensitivity and oxidative/inflammatory status) but also central features (BBB preservation and protection against inflammation) did not show any benefits of exercise. Indeed, there was a fast induction of irreversible brain damage that was more pronounced in exercise-trained ApoE-/- mice.